Elucidation of cellular functions of the Deubiquitinases USP53 and USP54 - Gallant, Kai (Technische Universität Dortmund, 2025)
Ubiquitylation is a reversible post-translational modification that is vital to most cellular processes. Deubiquitinases (DUBs), which modulate ubiquitylation, thus fulfil a critical role in maintaining a healthy cell state. Consequently, numerous pathological conditions are associated with misregulated or mutated DUBs. Two enzymes that have been linked to human pathologies are USP53 and USP54, two poorly characterised ubiquitin-specific protease (USP) family members which were annotated as catalytically inactive pseudoenzymes. Rudimentary knowledge about the cellular roles of USP53 and USP54 and limited insights into their potential substrates has, however, hampered a better understanding of their association with the reported diseases and phenotypes. The endeavour to better understand both proteins in this dissertation began by establishing enzymatic activity of both proteins. In subsequent experiments, the herein presented work thus focused on filling the knowledge gap between DUB activity and reported pathologies. As such, this dissertation provides a model that establishes a link between USP53 mutations and cholestasis as well as hearing loss. This was achieved by a combination of cell biological approaches, state-of-the-art mass spectrometry and a variety of enrichment tools allowing for the isolation and subsequent enzymatic treatment of ubiquitinated proteins. These methods facilitated the identification of two tricellular junction proteins, MARVELD2 and LSR, as substrates of USP53. For MARVELD2, significantly increased K63-linked ubiquitination upon depletion of the DUB could be demonstrated. Notably, the most prominent ubiquitinated species found to be emerging in these conditions is diubiquitinated MARVELD2, thus converging with in vitro work conducted within the group. Furthermore, this dissertation provides insights into the cellular functions of USP54, highlighting its role in cell cycle regulation and microtubule network organisation. In order to relate these phenotypic effects to catalytic activity, ubiquitin enrichment coupled to mass spectrometry was optimised which identified a set of proposed substrates. In addition, proximity labelling revealed USP54 interactors that localise to three discrete cellular compartments, centrioles, tight junctions and endolysosomal membranes. Orthogonal experiments furthermore supported interaction of the DUB with 14-3-3 proteins which indicates a regulation of USP54 protein abundance during the cell cycle. In conclusion, this work advances the knowledge about the two underexplored DUBs USP53 and USP54, while demonstrating the utility of combinatorial ubiquitin enrichment approaches to study the nature of ubiquitination on DUB substrates. The findings in conjunction with the reported pathologies will pave the way to better understand the association of DUB and diseases and potentially allow hijacking USP54 for novel therapeutic opportunities.
Keywords: Deubiquitinases; Proteomics; Ubiquitin; Cancer; Cholestasis; Hearing loss; USP; 570; 540; Ubiquitin